Comparative evaluation of bonding strength of computer aided machined ceramic, pressable ceramic, and milled metal implant abutment copings and effect of surface conditioning on bonding strength: An in vitro study - Sapna Rani; Mahesh Verma; Shubhra Gill; Rekha Gupta (Wolters Kluwer Medknow Publications, 2016)
Background/Purpose: The aim of this study was to compare the shear bond strength of computer aided design/computer aided machined ceramic (CAD/CAM), pressable ceramic, and milled metal implant copings on abutment and the effect of surface conditioning on bonding strength. Materials and Methods: A total of 90 test samples were fabricated on three titanium abutments. Among 90 test samples, 30 copings were fabricated by CAD/CAM, 30 by pressable, and 30 by milling of titanium metal. These 30 test samples in each group were further subdivided equally for surface treatment. Fifteen out of 30 test samples in each group were surface conditioned with airborne particle abrasion. All the 90 test samples were luted on abutment with glass ionomer cement. Bonding strength was evaluated for all the samples using universal testing machine at a crosshead speed of 5 mm/min. The results obtained were compared and evaluated using one-way ANOVA with post-hoc and unpaired t-test at a significance level of 0.05. Results: The mean difference for CAD/CAM surface conditioned subgroup was 1.28 ± 0.12, for nonconditioned subgroup was 1.20 ± 0.11. The mean difference for pressable surface conditioned subgroup was 1.18 ± 0.04, and for nonconditioned subgroup was 0.75 ± 0.28. The mean difference for milled metal surface conditioned subgroup was 2.57 ± 0.58, and for nonconditioned subgroup was 1.49 ± 0.15. Conclusions: On comparison of bonding strength, milled metal copings had an edge over the other two materials, and surface conditioning increased the bond strength.